2020
DOI: 10.1016/j.isci.2020.100996
|View full text |Cite
|
Sign up to set email alerts
|

Infants Show Physiological Responses Specific to Parental Hugs

Abstract: Summary Caregivers hug their infants to express affection and joy. However, it remains unknown how infants react to being hugged. Here we examined heart rate responses in first-year infants during a hug, hold, and tight hug from parents. Infants older than four months showed an increased R-R interval (RRI) during a hug, indicating reduced heart rates and pronounced parasympathetic activity. Few head movements predicted a higher RRI increase in infants during a parental hug compared with that during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…6 Several studies have successfully monitored cardiac parameters to assess the calming response to nonpharmacological interventions in preterm infants and in infants aged up to 12-month-old during distress situations. 7 16 Crying reduction or cessation induced by parental soothing was typically accompanied by a decrease in HR and or an increase in HRV as shown in groups of 69 infants aged 0–6 months, 16 of 53 infants aged 4–12 months, 17 and 12 infants aged 1–6 months. 11 Similarly, reduction of the stress response after painful medical procedures at the hospital in young populations was reflected by the modulation of cardiac parameters induced by interventions such as music, 7 , 18 kangaroo care, 9 , 19 , 20 or sucrose intake.…”
Section: B Ackgroundmentioning
confidence: 92%
“…6 Several studies have successfully monitored cardiac parameters to assess the calming response to nonpharmacological interventions in preterm infants and in infants aged up to 12-month-old during distress situations. 7 16 Crying reduction or cessation induced by parental soothing was typically accompanied by a decrease in HR and or an increase in HRV as shown in groups of 69 infants aged 0–6 months, 16 of 53 infants aged 4–12 months, 17 and 12 infants aged 1–6 months. 11 Similarly, reduction of the stress response after painful medical procedures at the hospital in young populations was reflected by the modulation of cardiac parameters induced by interventions such as music, 7 , 18 kangaroo care, 9 , 19 , 20 or sucrose intake.…”
Section: B Ackgroundmentioning
confidence: 92%
“…Because olfactory, visual, and auditory conditions were constant during these three tasks, the only difference was the tactile sensation. The RRI increase was higher during a hug from the parents than that from a female stranger ( Figure 3 B), which suggests that infants' autonomic responses are dependent on their social context ( Yoshida et al., 2020 ). Moreover, it was shown that infants recognize and prefer both their mother's and father's hugs, as the physical pressure on the infant when being hugged was different between the mother's and father's hugs.…”
Section: Neutral Sensory Processing During Huggingmentioning
confidence: 94%
“…How does the infant feel when being hugged? As this question could not be assessed by facial expressions or verbal cues, we recorded an electrocardiogram during a certain sequence of hug/hold sessions and examined time- and frequency-domain heart rate parameters ( Yoshida et al., 2020 ). The participants were instructed to perform three behavioral tasks for 20 s each: to hold the infant lightly as usual (hold); to hug the infant while thinking that the infant is adorable, not mechanically (hug); and to hold the infant very tightly as if the mother could run fast while holding the infant (tight hug).…”
Section: Neutral Sensory Processing During Huggingmentioning
confidence: 99%
See 2 more Smart Citations